Epidemiology of COPD - Mannino, David (Henry Stewart Talks, 2012)
GOLD guidelines for COPD, Lung function categories, BOLD initiative, Exacerbation rates for COPD patients, Hospitalization rates for COPD patients, Reasons for mortality in COPD patients, Update interview: An expanded definition of COPD from COPDGene, Update interview: Key lung function trajectories in the development of COPD, Update interview: Overlap syndromes with COPD, including asthma, pulmonary fibrosis, obstructive sleep apnea, Update interview: Combination therapies in the treatment of COPD, Update interview: Improvement in COPD metrics (hospitalization and mortality)
Updated at 2021/06/27